Inequality, Finance and Pro-Poor Investment in Africa - Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2015)
This study complements existing literature by investigating how investment-driven finance affects inequality in Africa. The empirical evidence is based on restricted and unrestricted Two-Stage Least Squares and a pre-crisis periodicity (1980-2002). Inequality is measured with estimated household income inequality whereas financial development is proxied with financial depth (money supply and liquid liabilities), financial efficiency (at banking and financial system levels), financial activity (from banking and financial system perspectives) and financial size. The findings show that with the exception of foreign investment, financial dynamics of depth, efficiency, activity and size enhance equalizing income-distribution through domestic, private and public investment channels. Policy implications are discussed with particular emphasis on improving inclusive development for the post-2015 sustainable development agenda. Notably, in the current transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs), mobilizing domestic resources for investment purposes may have greater inclusive benefits than overly reliance on foreign sources of capital.
Keywords: D60; E25; G20; I30; O55; 330; Finance; Investment; Poverty; Inequality; Africa